USE OF SOFTWARE "ANALYTICAL GEOMETRY" IN GIVING OF LECTION LESSONS (Journal of Information Technologies in Education (ITE), 2010)
In article are considered the questions of using of the software "Analytical geometry" in giving of lection lessons of analytical geometry in the higher school.
Keywords: information technologies; methodic of teaching course of analytical geometry; pedagogical software